Strong association between glucocerebrosidase mutations and Parkinsons disease in Sweden - Ran, Caroline; Brodin, Lovisa; Forsgren, Lars; Westerlund, Marie; Ramezani, Mehrafarin; Gellhaar, Sandra; Xiang, Fengqing; Fardell, Camilla; Nissbrandt, Hans; Söderkvist, Peter; Puschmann, Andreas; Ygland, Emil; et al. (Neurobiology of Aging, 2016)
Several genetic studies have demonstrated an association between mutations in glucocerebrosidase (GBA), originally implicated in Gauchers disease, and an increased risk of Parkinsons disease (PD). We have investigated the possible involvement of genetic GBA variations in PD in the Swedish population. Three GBA variants, E326K, N370S, and L444P were screened in the largest Swedish Parkinson cohort reported to date; 1625 cases and 2025 control individuals. We found a significant association with high effect size of the rare variant L444P with PD (odds ratio 8.17; 95% confidence interval: 2.51-26.23; p-value = 0.0020) and a significant association of the common variant E326K (odds ratio 1.60; 95% confidence interval: 1.16-2.22; p-value = 0.026). The rare variant N370S showed a trend for association. Most L444P carriers (68%) were found to reside in northern Sweden, which is consistent with a higher prevalence of Gauchers disease in this part of the country. Our findings support the role of GBA mutations as risk factors for PD and point to lysosomal dysfunction as a mechanism contributing to PD etiology. (C) 2016 The Author(s). Published by Elsevier Inc. Funding Agencies|Swedish Brain Power; Swedish Research Council [K2013-99X-22248-01-3]; Swedish Parkinson Foundation [613/13, 712/14]; Swedish Brain Foundation [FO2013-0213]; Ake Wibergs Stiftelse [756194137]; Karolinska Institutet Funds [2013fobi37223]; Karolinska DPA within the Swedish National Health Services (ALF); Neurology Department Karolinska University Hospital 100-year Fund; ERC Advanced Investigator Grant [322744]; Swedish Parkinson Academy; Umea University (Insamlingsstiftelsen); Bundy Academy, Sweden; Lions Research Foundation Skane; Elsa Schmitz Stiftelse; Skane University Hospital Foundations; Donations program, NEURO forbundet, Sweden